Study of Methylation Pattern of APC Gene as Epigenetic Biomarker in Lung Cancer Patients - Singh, Jagdeep (Research Journal Biotechnology, 2008)
A malignant tumor results after a series of DNA alterations in a single cell4, or clones of that cell, which lead to loss of normal function, aberrant or uncontrolled cell growth and often metastases12. Several of the genes, which are frequently lost or mutated, have been identified including those whose function is to induce cell proliferation under specific circumstances (e.g. ras and ntyc proto-oncogenes) and genes which are programmed to halt proliferation in damaged cells (e.g. p53 and APC tumour suppressor genes6). Other mutations are also necessary, in genes involved in DNA repair, cell-cycle control, angiogenesis and telemorase production. With the exception of rare familial cancers which are primarily caused by a germline inheritance of a specific mutation, a sporadic cancer may acquire mutations as a result of genotoxic exposure to external or internal agents (such as tobacco, carcinogens, dietary factors, pollutants and sex hormones) and consequent DNA aberrations9. The likelihood of a mutation occurring and persisting in subsequent clones may be heavily dependant on the efficiency with which potentially toxic exposures are metabolized and excreted and also the efficiency with which small mistakes in DNA replication are rectified13. This progress of carcinogenesis is likely to vary strongly between individuals because of the population variability in polymorphic genes that regulate these processes. Changes in the patterns of methylation1 have been associated with the altered expression of a number of genes involved in cell cycle control and apoptosis, including p161NK4a3 RASSFIA, RAR-Β, FHIT, APC, H- and E-cadherins2 among many others in various carcinomas, including lung cancer. Silencing of tumor suppressor and tumor-related genes by hypermethylation at promoter CpG islands1.7 is one of the major events in human tumorigenesis. In this study the methylation pattern of APCgene was studied in 25 lung cancer patients who included active, passive as well as subjects who had left smoking. Ae results signify that the methylation pattern can be designated as epigenetic biomarker14 in lung cancer patients5 where the diagnosis is not well defined in the early stages of tumongenesis.
Only IISERM authors are available in the record.
Keywords: APC gene; Lung cancer; Epigenetic biomarker